Apakah Dewan Komisaris Independen Mempunyai Peran Sebagai Variable Moderasi atas Related Party Transaction, Struktur Modal dan Ukuran Perusahaan terhadap Nilai Perusahaan? - Maryanti, Eny; Magfiroh, Nailil (Department of Accounting, Faculty of Economics & Business, 2024)
The aim of this study is to investigate the effects of related party transactions and overall business value on capital structure, company size, and an independent board of commissioners. The manufacturing businesses in the food and beverage subsector that were listed on the Indonesia Stock Exchange between 2017 and 2021 are the focus of this study. The research sample consisted of 60 data points from 12 firms that fulfilled predefined parameters, chosen through the use of purposeful sampling. This study employs a quantitative methodology, with Eviews software serving as the analysis tool. The study's findings demonstrate that the value of a firm is not significantly impacted by transactions involving related parties. On the other hand, a company's value is greatly influenced by its size and capital structure. The independent board of commissioners does not lessen the effect that capital structure and related party transactions have on the value of the company. Nonetheless, the effect of a company's size on its value might be lessened by an impartial board of commissioners. The following policies can be implemented by the business world based on the consequences of the research: First, the business sector needs an optimal capital structure, which includes using debt with suitable limits, in order to draw investors and build company value. In addition, using debt might lessen the tax liability of the business. Secondly, in order to draw in investors, big businesses need to manage their assets well.